Validity and reliability of pre-class reading tasks for waves and optics (PRT-WO) - Asrab Ali Nur Faralina; Ayop Shahrul Kadri; Abdullah Nurul Syafiqah Yap (Program Pascasarjana Universitas Negeri Yogyakarta & HEPI, 2016)
This study aims to produce a valid and reliable instrument in preparing students prior to class at university level of introductory Waves and Optics course. The instrument so called Pre-class Reading Task for Waves and Optics (PRT-WO) was used to probe students’ knowledge acquired through targeted reading activities. In practice, PRT-WO was given in a series before actual face-to-face class as a reading assignment. PRT-WO was content validated through expert review which was analyzed using the interrater reliability Cohen’s kappa. An item analysis was done to identify inappropriate items further evaluated using the reliability test of Kuder-Richardson 20 (KR20). The finding reveals that the value of kappa is 0.66 and the value of KR20 is 0.68, indicating that the developed instrument is valid and reliable.